2005
DOI: 10.1681/asn.2004121062
|View full text |Cite
|
Sign up to set email alerts
|

Increased Osteoblastic Activity and Expression of Receptor Activator of NF-κB Ligand in Nonuremic Nephrotic Syndrome

Abstract: Patients with nephrotic syndrome (NS), even with normal GFR, often display altered mineral homeostasis and abnormal bone histology. However, the latter, mostly osteomalacia and increased bone resorption, cannot be readily explained by the prevalent concentrations of parathyroid hormone and vitamin D metabolites. The transmembrane receptor activator of NF-B ligand (RANKL) of osteoblasts is essential for osteoclast formation and differentiation. Osteoblasts activity and the expression of RANKL were tested in cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 48 publications
2
9
0
5
Order By: Relevance
“…In fact, up-regulation of the osteoclastactivator receptor activator of nuclear factor k-B ligand (RANKL), an important mechanism of bone loss independent of Cy, was recently demonstrated in normal human osteoblasts exposed to sera from children with active NS. 57 The findings in the present study of normal BMD in most patients during Cy-Rx and while in clinical remission, challenge the notion of a primary role of Cy in the bone loss of Tx patients 49 and point to the importance of other preexisting or concurrent factors independent of Cy as causes for the bone loss. 1,48,57 …”
Section: Discussionsupporting
confidence: 39%
See 1 more Smart Citation
“…In fact, up-regulation of the osteoclastactivator receptor activator of nuclear factor k-B ligand (RANKL), an important mechanism of bone loss independent of Cy, was recently demonstrated in normal human osteoblasts exposed to sera from children with active NS. 57 The findings in the present study of normal BMD in most patients during Cy-Rx and while in clinical remission, challenge the notion of a primary role of Cy in the bone loss of Tx patients 49 and point to the importance of other preexisting or concurrent factors independent of Cy as causes for the bone loss. 1,48,57 …”
Section: Discussionsupporting
confidence: 39%
“…57 The findings in the present study of normal BMD in most patients during Cy-Rx and while in clinical remission, challenge the notion of a primary role of Cy in the bone loss of Tx patients 49 and point to the importance of other preexisting or concurrent factors independent of Cy as causes for the bone loss. 1,48,57 …”
Section: Discussionsupporting
confidence: 39%
“…This result was unexpected because OPG inhibits osteoclastogenesis. The association of RANKL with elevated bone resorption has already been suggested in other studies that involved molecular biology techniques and focused on other renal or nonrenal diseases (37)(38)(39)(40); however, reports of serum concentration of OPG have shown OPG to be significantly higher rather than lower in women with postmenopausal osteoporosis than in age-matched control subjects (41,42), what the authors attributed to a compensatory response to the enhanced bone resorption. Because immunohistochemical studies in human bone tissue quantifying RANKL or OPG are scant, the hypothesis of a higher bone expression of OPG counteracting RANKL at a bone level presently observed may be raised on basis of the results of serum levels of cytokines (41).…”
Section: Discussionmentioning
confidence: 90%
“…Freundlich et al [21] observed an up-regulation of RANKL in normal osteoblasts incubated with sera of NS children in relapse and normal expression in those incubated with sera of NS children in remission; this result suggests that changes in RANKL expression in NS children are transient and reversible. The study of Faienza et al [22] showed a down-regulation of OPG and over-expression of RANKL in T-cells from patients with a 21-hydroxylase deficiency who were treated with GCS, compared with controls.…”
Section: Discussionmentioning
confidence: 99%